2013
DOI: 10.3171/2013.4.focus1335
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial hemorrhage from dural arteriovenous fistulas: clinical features and outcome

Abstract: Object In this paper the authors' goal was to review the clinical features and outcome of patients with intracranial dural arteriovenous fistulas (DAVFs) who presented with hemorrhage. Methods A retrospective study of 28 patients with DAVFs who presented with intracranial hemorrhage to 2 separate institutions was performed. The information reviewed included clinical presentation, location and size of hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 15 publications
2
35
0
Order By: Relevance
“…Similarly, Aviv et al [2] found that a venous varix was present in 7 (35%) of the 20 cervical dural AVF patients presenting with subarachnoid hemorrhage, compared with 1 (5%) in the nonhemorrhage group. These findings have been corroborated in a series of intracranial dural AVFs [109]. In our patient, the rate of arteriovenous transit was faster than that of other patients presenting without hemorrhage (1 vs. 2-3 [29] 20 0 0 Blackburn et al [30] 17 0 0 Bl ehaut et al [31] 10 0 0 Bowen et al [32] 8 0 0 Bradac et al [33] 13 0 0 Burrows et al [34] 1 0 0 Cabrera et al [35] 1 0 0 Cenzato et al [36] 37 0 0 Cenzato et al [37] 1 0 0 Cordato et al [38] 1 0 0 Criscuolo et al [39] 1 0 0 Deen et al [40] 1 0 0 Eskandar et al [41] 18 0 0 Finsterer et al [42] 1 0 0 Foote et al [43] 1 0 0 Gilbertson et al [44] 55 0 0 Hage et al [45] 5 0 0 Hall et al [46] 3 0 0 Hanakita et al [47] 2 0 0 Hassler et al [48] 18 0 0 Hasuo et al [49] 2 0 0 Houdart et al [50] 1 0 0 Huffmann et al [51] 18 0 0 Hurst et al [ seconds), and the draining vein was associated with a venous varix (Figs.…”
Section: Discussionsupporting
confidence: 67%
“…Similarly, Aviv et al [2] found that a venous varix was present in 7 (35%) of the 20 cervical dural AVF patients presenting with subarachnoid hemorrhage, compared with 1 (5%) in the nonhemorrhage group. These findings have been corroborated in a series of intracranial dural AVFs [109]. In our patient, the rate of arteriovenous transit was faster than that of other patients presenting without hemorrhage (1 vs. 2-3 [29] 20 0 0 Blackburn et al [30] 17 0 0 Bl ehaut et al [31] 10 0 0 Bowen et al [32] 8 0 0 Bradac et al [33] 13 0 0 Burrows et al [34] 1 0 0 Cabrera et al [35] 1 0 0 Cenzato et al [36] 37 0 0 Cenzato et al [37] 1 0 0 Cordato et al [38] 1 0 0 Criscuolo et al [39] 1 0 0 Deen et al [40] 1 0 0 Eskandar et al [41] 18 0 0 Finsterer et al [42] 1 0 0 Foote et al [43] 1 0 0 Gilbertson et al [44] 55 0 0 Hage et al [45] 5 0 0 Hall et al [46] 3 0 0 Hanakita et al [47] 2 0 0 Hassler et al [48] 18 0 0 Hasuo et al [49] 2 0 0 Houdart et al [50] 1 0 0 Huffmann et al [51] 18 0 0 Hurst et al [ seconds), and the draining vein was associated with a venous varix (Figs.…”
Section: Discussionsupporting
confidence: 67%
“…Since venous varices are often the source of hemorrhage, the hemorrhage can be remote from the actual location of the AV shunt. 29 …”
Section: Imagingmentioning
confidence: 99%
“…In fact, the overwhelming majority of patients with DAVFs who present with hemorrhage have TDAVFs. 5 It is now recognized that the presence of retrograde leptomeningeal drainage, not DAVF location, is the major determining factor of the mode of clinical presentation, and TDAVFs are universally associated with retrograde leptomeningeal drainage. 11 The natural history of symptom- atic DAVF with retrograde leptomeningeal drainage is particularly unfavorable.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, these lesions are treated aggressively on diagnosis. [3][4][5] Traditionally, surgical resection was the only treatment available for these lesions. However, endovascular embolization, either alone or in combination with surgery, is increasingly used.…”
mentioning
confidence: 99%